Efforts to Improve Science Learning Outcomes Through the Problem-Based Learning Model for Students in Bengkulu - Sukarno, Sukarno (Journal of Basic Education Research, 2024)
Purpose of the study: This research aims to address the low student learning outcomes in the science learning subjects of class IV elementary school students in Bengkulu by applying the Problem Based Learning model and examining its effectiveness in enhancing the student learning outcome. Methodology: The research uses a Classroom Action Research method with two cycles, each consisting of planning, implementation, evaluation and reflection stages. The research subjects are 20 students in class IV Elementary School in Bengkulu. The data collection technique is a test. Main Findings: The research data shows that the Problem Based Learning model can improve the learning outcomes of class IV elementary school students in Bengkulu. The completeness of learning outcomes increases from 3% in the pre-cycle to 65% in the first cycle and 85% in the second cycle, exceeding the expected outcome of 75%. Novelty/Originality of this study: The novelty in this research is the application of the Problem Based Learning model in the science learning subjects of class IV elementary school students in Bengkulu, which have different characteristics and needs from other students in other regions or countries. The research also contributes to the development of the Classroom Action Research method, which involves the active participation of the teacher and the students in the learning process and the improvement of the learning quality. The research has implications for the improvement of the science curriculum and the teacher training program in Bengkulu.